W±-boson production in p-Pb collisions at √sNN=8.16 TeV and Pb-Pb collisions at √sNN= 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Journal of high energy physics, 2023)
The production of the W± bosons measured in p-Pb collisions at a centre-of-mass energy per nucleon–nucleon collision = 8.16 TeV and Pb–Pb collisions at = 5.02 TeV with ALICE at the LHC is presented. The W± bosons are measured via their muonic decay channel, with the muon reconstructed in the pseudorapidity region −4 < < −2.5 with transverse momentum > 10 GeV/c. ...
Im Titel ist "NN" nach "s" tiefgestellt, der ganze Ausdruck "sNN" steht unter dem Wurzelsymbol
ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y.C. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S. Stiefelmaier, M. Völkl, B. Windelband, A. Yuncu, F. Zanone [und 1009 weitere]
Gesehen am 09.11.2023